Avoiding litigation in the age of telemedicine. Issue 3 (16th May 2022) - Desai, Chaitya; Modgil, Vaibhav; Pearce, Ian
Abstract : Since the COVID‐19 pandemic, telemedicine has provided a lifeline for non‐emergency healthcare provision. However, with its widespread implementation, many clinicians wonder what the litigation considerations might be for telemedicine. This paper reviews the legal cases that have shaped UK clinical negligence legislation and their application to telemedicine. Key considerations for avoiding litigation are also outlined.